-x-3=-4x-9

Simple and best practice solution for -x-3=-4x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-3=-4x-9 equation:


Simplifying
-1x + -3 = -4x + -9

Reorder the terms:
-3 + -1x = -4x + -9

Reorder the terms:
-3 + -1x = -9 + -4x

Solving
-3 + -1x = -9 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-3 + -1x + 4x = -9 + -4x + 4x

Combine like terms: -1x + 4x = 3x
-3 + 3x = -9 + -4x + 4x

Combine like terms: -4x + 4x = 0
-3 + 3x = -9 + 0
-3 + 3x = -9

Add '3' to each side of the equation.
-3 + 3 + 3x = -9 + 3

Combine like terms: -3 + 3 = 0
0 + 3x = -9 + 3
3x = -9 + 3

Combine like terms: -9 + 3 = -6
3x = -6

Divide each side by '3'.
x = -2

Simplifying
x = -2

See similar equations:

| x(-2)=(-18) | | x-8=-2x+22 | | 5(a+4)-3.2=14.3 | | x-16=-x-30 | | 5x-4=-2x-25 | | -3x-17=-44 | | 8x-7=3x-17 | | x+(.4x*.5x*.145x)=19130 | | Y=-0.8t+40 | | 8x+14=4x+34 | | 113-303= | | 33(-5)= | | 6=-10d+2 | | 33x-5= | | 2x^2-4x+103=0 | | 2x^2-4x-103=0 | | 6-7d=-3D+2 | | 15-2x=0 | | -6x^2-2x-1=0 | | 8=-5x-3 | | -366+k=170 | | 17+4(3+q)-a= | | 3x-5(0.6x-1)=3 | | 4(3+9)+10a-41= | | M+-2=67 | | 6x-24=4x-2-6 | | 2(3-3x)=94 | | 6x+8+2x=4(5+x) | | 3f+47-2f=40 | | 2-(2x-1)+7x=10 | | 5x+22=100+3x | | 6x-3(0.2x+3)=2x |

Equations solver categories